An exploratory study of the long-term impact of difficulty kneeling after total knee replacement. Issue 7 (27th March 2019) - Fletcher, Daniel; Moore, Andrew J.; Blom, Ashley W.; Wylde, Vikki
Abstract: Purpose: To explore the long-term impact of difficulty with kneeling and how healthcare services could be improved to help patients kneel after total knee replacement. Patients and methods: Telephone interviews were conducted with 56 patients who had extreme difficulty kneeling at 7–10 years after knee replacement. Patients were asked about reasons for difficulty kneeling, how it impacted upon their lives, and experiences of healthcare services. Responses were recorded on a standardized proforma and a descriptive content analysis performed. Results: Most people had difficulty kneeling because of pain or discomfort in the replaced knee. Many patients described how this limitation affected their daily lives, including housework, gardening, religious practices, leisure activities and getting up after a fall. Patients often adapted to these limitations by finding alternatives to kneeling, assistance from others or home adaptations. Many patients had accepted that they could not kneel, however some still expressed frustrated. Few patients had consulted with healthcare professionals about kneeling difficulties, and unmet needs included the provision of information about kneeling and post-operative physiotherapy. Interpretation: This study provides an initial insight into how difficulty kneeling after knee replacement impacts upon patientsand the need for better healthcare provision. Implications for rehabilitation: Rehabilitation professionals should be aware that many patients experience difficulty with kneeling after total knee replacement and that this has a long-term impact upon patients. There is a need for rehabilitation after knee replacement to address kneeling difficulties. It is suggested that this rehabilitation should be delivered early in the postoperative recovery phase and designed to address the multifactorial reasons that patients find kneeling problematic.